2019
DOI: 10.14710/ijfst.14.2.128-135
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS HUBUNGAN SUHU PERMUKAAN LAUT DAN KLOROFIL-A CITRA SATELIT SUOMI NPP VIIRS TERHADAP HASIL TANGKAPAN PURSE SEINE DI PPN PENGAMBENGAN, BALI (Analysis of the Relationship of Sea Surface Temperature and Chlorophyll-a The Suomi NPP VIIRS Satellite Image Against the Catch of the Seine Purse in PPN Pengambengan, Bali)

Abstract: ABSTRAKPerikanan Tongkol (Euthynnus affinis) di Perairan Selat Bali berkembang pesat sejak diperkenalkannya alat tangkap Purse seine, hal tersebut menyebabkan semakin meningkatnya jumlah armada kapal penangkap ikan. Meskipun upaya penangkapan meningkat, akan tetapi hasil tangkapan yang didapatkan menurun. Untuk tujuan tersebut diperlukan kajian yang mendalam tentang pola sebaran suhu permukaan laut dan klorofil-a, agar ke depan dapat diketahui daerah penangkapan ikan Tongkol. Penelitian ini mengkaji perbedaan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…3, high chlorophyll-a concentrations in April 2019 and 2020 will be followed by high catches in the following 2-3 months. According to Ghufron et al [7] and Syahdan et al [11], the value of chlorophyll-a concentration found in waters can be used as an indication to determine the abundance of fish resources in the sea, but sometimes it is also not directly proportional to the catch obtained. This is because chlorophyll-a takes time to be eaten first by herbivorous fish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, high chlorophyll-a concentrations in April 2019 and 2020 will be followed by high catches in the following 2-3 months. According to Ghufron et al [7] and Syahdan et al [11], the value of chlorophyll-a concentration found in waters can be used as an indication to determine the abundance of fish resources in the sea, but sometimes it is also not directly proportional to the catch obtained. This is because chlorophyll-a takes time to be eaten first by herbivorous fish.…”
Section: Resultsmentioning
confidence: 99%
“…Satellite imagery data that has been obtained requires verification with in situ data so that the data obtained becomes more accurate. According to Ghufron et al [7], stating that satellite image data is needed verification with in situ data so that the value of accuracy and feasibility of a data is known. The step to verification is to correct relative errors.…”
Section: Image Data Verificationmentioning
confidence: 99%
“…Several studies have tried to examine the effect of oceanographic parameters such as surface temperature, currents, salinity, and chlorophyll-a concentration based on remote sensing and geographic Information systems (Arrizabalaga et al 2015;Ghufron et al 2019;Seloi et al 2019) and information based on local knowledge of fishermen (Moreno et al 2007;Macusi et al 2017;Jauharee et al 2021), including the use of GPS buoys to FADs (Irineo et al 2014;Lopez et al 2014;Maufroy et al 2016), providing initial information on potential pelagic fishing zones and habitat distribution of fish in the fishing ground. The results of this study also provide a general description of the influence of oceanographic parameters on fish distribution, but the scope of the research is still for a large area and has not been able to provide a more specific description of the behavior of fish in the FADs area itself as a media for purse seine catching aids.…”
Section: Introductionmentioning
confidence: 99%
“…Secara umum keberadaannya kawanan ikan dengan agregasinya, karena pengaruh faktor fisika dan kimia khususnya kondisi oseanografi suatu wilayah (Arrizabalaga et al, 2015;Seloi et al, 2019;Ghufron et al, 2019), ditinjau dari aspek biologi keberadaan spesies ikan pada areal rumpon tersebut memang ada hubungannya (Bubun et al, 2015;Irawati et al, 2021), yang dapat mempengaruhi agresi dan tingkah laku ikannya (Capello et al, 2016;Lopez et al, 2017;Orue, et al, 2019).…”
unclassified